2011
DOI: 10.3758/s13421-011-0117-9
|View full text |Cite
|
Sign up to set email alerts
|

Source-constrained retrieval influences the encoding of new information

Abstract: Jacoby, Shimizu, Daniels, and Rhodes (Psychonomic Bulletin & Review, 12, 852-857, 2005) showed that new words presented as foils among a list of old words that had been deeply encoded were themselves subsequently better recognized than new words presented as foils among a list of old words that had been shallowly encoded. In Experiment 1, by substituting a deep-versus-shallow imagery manipulation for the levels-of-processing manipulation, we demonstrated that the effect is robust and that it generalizes, also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 20 publications
2
34
3
Order By: Relevance
“…Our behavioral findings replicated earlier studies in demonstrating the typical foil effect: Semantic foils were remembered significantly more accurately than non-semantic foils, supporting the idea that participants implemented a semantic processing mode during the semantic memory test (Alban & Kelley, 2012;Danckert et al, 2011;Halamish et al, 2012;Jacoby et al, 2005a;2005b;Kantner & Lindsay, 2013;Marsh et al, 2009;Vogelsang et al, 2016). Time-frequency analysis of EEG data collected during the initial study phase revealed a power decrease in alpha frequencies over left frontal electrodes between 600-1000ms (and mid/right posterior electrodes between 600-1600ms) during the semantic as opposed to non-semantic task, consistent with prior literature highlighting a role for alpha oscillations in semantic processing (e.g.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our behavioral findings replicated earlier studies in demonstrating the typical foil effect: Semantic foils were remembered significantly more accurately than non-semantic foils, supporting the idea that participants implemented a semantic processing mode during the semantic memory test (Alban & Kelley, 2012;Danckert et al, 2011;Halamish et al, 2012;Jacoby et al, 2005a;2005b;Kantner & Lindsay, 2013;Marsh et al, 2009;Vogelsang et al, 2016). Time-frequency analysis of EEG data collected during the initial study phase revealed a power decrease in alpha frequencies over left frontal electrodes between 600-1000ms (and mid/right posterior electrodes between 600-1600ms) during the semantic as opposed to non-semantic task, consistent with prior literature highlighting a role for alpha oscillations in semantic processing (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Because semantic encoding typically leads to more accurate memory compared to non-semantic encoding, this "foil effect" implies that participants strategically orient their retrieval towards a semantic processing mode when attempting to retrieve semantic encoded information, and a non-semantic processing mode when retrieving nonsemantic information, resulting in better incidental encoding of semantic compared to nonsemantic foils. Jacoby and colleagues interpreted this foil finding in light of the transfer appropriate processing principle by emphasizing the importance of the overlap in study-test operations for optimizing retrieval success (see also Alban and Kelley, 2012;Danckert et al, 2011;Gray & Gallo, 2015;Halamish et al, 2012;Kantner and Lindsay, 2013;Marsh et al, 2009;Zawazka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the memory--for--foils literature, the pleasantness task has been most often used as the deep orienting task so the majority of evidence for the consequences for foils of adopting retrieval orientation has come from this particular task. Still, there are studies that investigated the memory--for--foils phenomenon with other tasks requiring deep processing of targets (Alban & Kelley, 2012;Danckert et al, 2011) and given comparable results obtained in those studies, the idea of the uniqueness of the pleasantness task is unlikely to be correct.…”
Section: Discussionmentioning
confidence: 99%
“…All previous investigations of retrieval orientation with the memory--for--foils paradigm focused on a comparison of deep and shallow processing tasks. Importantly, Danckert et al (2011) showed that retrieval orientation is likely to be adopted only for a deep test, but not necessarily on a shallow test. As mentioned earlier, in their study, foils from the deep and shallow tests were subjected to the same judgments that defined deep and shallow tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation